One-Year Change in the H2FPEF Score After Catheter Ablation of Atrial Fibrillation in Patients With a Normal Left Ventricular Systolic Function - Kim, Min; Yu, Hee Tae; Kim, Tae-Hoon; Uhm, Jae-Sun; Joung, Boyoung; Lee, Moon-Hyoung; Pak, Hui-Nam (Frontiers in Cardiovascular Medicine, 2021)
Background: It is unclear whether atrial fibrillation (AF) catheter ablation (AFCA) improves the left ventricular (LV) diastolic function. We evaluated the 1-year change in the H2FPEF score, which reflects the degree of LV diastolic function, after AFCA among patients with a normal LV systolic function. Methods and Results: We included 1,471 patients (30.7% female, median age 60 years, paroxysmal-type AF 68.6%) who had available H2FPEF scores at baseline and at 1-year after AFCA to evaluate the 1-year change in the H2FPEF score (H2FPEF score[1-yr]) after AFCA. Baseline high H2FPEF scores (≥6) were independently associated with the female sex, left atrium (LA) diameter, LV mass index, pericardial fat volume, and a low estimated glomerular filtration rate. One-year after AFCA, decreased H2FPEF scores[1-yr] were associated with baseline H2FPEF scores of ≥6 (OR, 4.19 [95% CI, 2.88-6.11], p<0.001), no diabetes (OR, 0.60 [95% CI, 0.37-0.98], p=0.04), and lower pericardial fat volume (OR, 0.99 [95% CI, 0.99-1.00], p=0.003). Increased H2FPEF scores[1-yr] were associated with a baseline H2FPEF score of <6 (OR, 3.54 [95% CI, 2.08-6.04], p<0.001) and sustained AF after a recurrence within one year (SustainAF[1-yr]; OR, 1.89 [95% CI, 1.01-3.54], p=0.048). Throughout a 56-month median follow-up, an increased H2FPEF score[1-yr] resulted in a poorer rhythm outcome of AFCA (at 1-year, log-rank p=0.003; long-term, log-rank p=0.010). Conclusions: AFCA appears to improve LV diastolic dysfunction. However, SustainAF[1-yr] may contribute to worsening LV diastolic dysfunction and it was shown by increased H2FPEF scores[1-yr] which were independently associated with a higher risk of AF recurrence rate after AFCA. (ClinicalTrials.gov Identifier: NCT02138695)